STUDENTS’ DIFFICULTIES IN WRITING THESIS OF ENGLISH EDUCATION STUDY PROGRAM IN MUHAMMADIYAH UNIVERSITY OF SUMATERA BARAT - Hendrita, Rini; Ariani, Sri (TELL - US JOURNAL, 2022)
This research is about difficulties faced by the students in writing thesis at eight semester of English Education Study Program of Muhammadiyah University of Sumatera Barat. The purpose of the research is to describe the students’ difficulties in writing the thesis. The participants of this research were eight semester students of English Education Study Program of Muhammadiyah University of Sumatera Barat that consist of 15 students. This research is a descriptive research. It is aimed at describing things as the way and also analyzing the interrelationship of the data. The instrument used in this research was questioner and interview. The questioner is used to find out the students’ difficulties in writing thesis while the interview is used to support the data gotten from questioner. The result of this research shows that there are 13 difficulties faced by students in writing thesis. And the most frequent difficulties is “pouring ideas into scientific writing”. All of the students (15) faced this difficulty.